Optimizing Various Religious Activities to Increase Community Spirit of Ibadah Through Real Work Lecture Programs - Ade Muhammad Ritonga; Fattah Ali Syahputra Harahap; Muhammad Rafif Irfan; Muhammad Fajrul Abdul Manan; Hari Nurrachman (ASSUNNAH PRESS, 2024)
Ibadah is one of the essential elements in a Muslim's life because the essence of human creation is to Ibadah God. However, unfortunately, there are still many Muslim communities in North Sumatra Province that are weak and lack enthusiasm for carrying out the Ibadah. This article will explain the optimization of various religious activities to increase the community's Ibadah spirit. It will focus its research on Hamlet VIII, Besar II Village, Terjun, Pantai Cermin District, Serdang Bedagai Regency, North Sumatra Province. The research method used is the Participatory Action Research (PAR) method, an approach whose process aims to learn to overcome problems and fulfill the practical needs of society. The results of this research conclude that the various religious activities that have been carried out can increase the spirit of Ibadah of the people of Dusun VIII, Besar II Terjun Village, Pantai Cermin District, Serdang Bedagai Regency, North Sumatra Province through Real Work Lecture activities, by carrying out religious activities in the form of short lectures, Qiroatul Hadith (Reading Hadith), this recitation for children, Islamic boarding school express, and holding competitions to memorize short surahs and the call to prayer. The community revealed that the activities that have been carried out provided a positive response to increasing their enthusiasm for Ibadah